An Analysis of Speech Act Used On Habibie & Ainun 3 Movie Script - Isra Mariana Harahap (JURNAL LINER (Language Intelligence and Educational Research), 2022)
ABSTRACT: The purpose of this study was to find out: 1) the types of illocutionary speech act used in Habibie & Ainun 3 movie script,2) the most dominant illocutionary speech act used in Habibie & Ainun 3 movie script and 3) factors of using dominant illocutionary speech act in Habibie & Ainun movie script. By using speech act theory of John Rogers Searle. To analyze it, used note-taking and transcribing. The researcher focused to analyze illocutionary speech act that include 5 types, namely: Assertive, Directive, Commissive, Expressive, and Declarative. The result of the study showed that from Habibie & Ainun movie script, the researcher found there are 378 utterance containing the types of illocutionary act. Assertive with percentage 54.49%, next was followed by Directive 30.06%, next Expressive is 7.40%, Declarative 4.49%, and Declarative 0.52%. Based on the result of the study, it can be concluded that the most dominant types of illocutionary act in Habibie & Ainun movie script is Assertive. While for the factors of using dominant illocutionary act the researcher analyzed there is speaker’s belief, feeling or psychology, and desire or fulfill desire. Key Word: Speech Act, Illocutionary Act, Script, Movie ABSTRAK: Tujuan dari penelitian ini adalah untuk mengetahui: 1) jenis-jenis tindak tutur ilokusi yang digunakan dalam naskah film Habibie & Ainun 3, 2) tindak tutur ilokusi yang paling dominan yang digunakan dalam naskah film Habibie & Ainun 3, 3) faktor-faktor penggunaan tindak tutur ilokusi dominan yang digunakan dalam naskah film Habibie & Ainun 3. Dengan menggunakan teori tindak tutur dari John Roger Searle. Unyuk menganalisanya, digunakan pencatatn dan transkip. Peneliti memfokuskan untuk menganalisis tindak tutur ilokusi yang terdiri dari 5 jenis, yaitu: Asertif, Direktif, Komisif, Ekspresif, dan Deklaratif. Hasil dari penelitian ini menunjukkan bahwa dari naskah film Habibie & Ainun 3, peneliti menemukan 378 ucapan yang mengandung ilokusi. Asertif dengan persentase 54.49%, selanjutnya diikuti oleh Direktif 30.06%, selanjutnya Ekspresif 7.40%, Deklaratif 0.52%. Berdasarkan hasil penelitian, dapat disimpulkan bahwa jenis tindak tutur ilokusi yang paling dominan adalah Asertif. Sementara untul faktor-faktor penggunaan tindak tutur ilokusi yang paling dominant, peneliti menganalisis ada keyakinan pembicara, perasaan dan psikologi, dan keinginan atau pemenuhan keinginan. Kata Kunci: Tindak tutur, Tindak tutur ilokusi, naskah, film